PENGARUH MERGER TIGA BANK SYARIAH DAN FINTECH TERHADAP KEPUASAN NASABAH DI BSI KCP MOJOKERTO - Diana Ilkhafa; lu'lu'il Maknuun (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2023)
The purpose of this study was to analyze and find out the effect of the merger of three Islamic banks and fintech on customer satisfaction at BSI KCP Mojokerto Mojopahit 2 during the Covid-19 pandemic. The data used are primary data obtained through online questionnaires using Google Forms. The sample size used in this study was 91 respondents using a purposive sampling method. The data analysis used in this study is multiple linear regression analysis using SPSS 28. The results of this study indicate that: 1) The merger of three Islamic banks has a significant effect on customer satisfaction with a significant value of 0.001 <0.05 and t count (3.633) > t table (1987). 2) Fintech has a significant effect on customer satisfaction with a significant value of 0.001 <0.05 and t count (3.821) > t table (1.987). 3) The merger of three Islamic banks and fintech together has a significant effect on customer satisfaction with a significant value of 0.001 <0.05 and f count (12.677) > f table (3.10).